Pengidap Skizofrenia sebagai Mukallaf dalam Perspektif Fikih Islam: Schizophrenia as a Mukallaf from the Perspective of Islamic Fiqh - Sarni, Santi; Nurul Sri Wahyuni (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out the nature of schizophrenia and the view of Islamic jurisprudence towards people with schizophrenia asmukallaf. The problems that the author raises in this research are: first, what is the nature of schizophrenia; secondly, what is the view of Islamic jurisprudence towards people with schizophrenia asmukallaf. This research uses a qualitative descriptive (non-statistical) type of research, which focuses on the study of manuscripts and texts, using normative and sociological approach methods. The research results found were as follows: first, schizophrenia can cause varying symptoms in each individual, but the core symptoms include delusions, hallucinations, thought disorders and abnormal behavior. Schizophrenia can also cause impairment in an individual's academic, occupational and daily functioning. The factors that cause this disorder consist of genetic, environmental and psychological factors. Second, in the view of Islamic Jurisprudence, people with schizophrenia who have lost their minds are not punished as mukallaf or not burdened with taklif. It is not obligatory to perform prayers and fast. Except for those who still have awareness of their minds, they are obliged to perform prayers and fast. If you are unable to fast, you must replace your fast or pay fidyah. To review the extent of understanding of people with schizophrenia, a diagnosis is needed from professional mental health personnel, both doctors and psychologists. Maliyah obligations such as zakat still apply to guardians of relatives who must pay zakat. Because zakat obligations are related to obligations on assets, not bodies.